Towards Thinking by Teaching - Sirtautas, Vytautas (Acta Paedagogica Vilnensia, 2000)
The author of this article studies the modern tendencies of thinking research and its influence into didactics of mother language teaching in secondary school.
Keywords: Didactics; teaching; teaching of language; thinking.